The Mission - Ghia, Fernando; Goldcrest Films and Television Ltd.; Kingsmere Productions, Ltd.; Enigma Productions, Ltd. (Quezon City Viva Video, 2003)
Based on historical events that occurred around the borderlands of Argentina, Paraguay and Brazil in the year 1750, the drama concerns two men, a priest and a soldier, who unite to shield a South American Indian tribe from brutal subjugation by 18th century colonial empires.
Disc 1 (60 min.) -- disc 2 (1 hr., 3 min.)
VCD.
Original story and screenplay by Robert Bolt ; produced by Fernando Ghia and David Puttnam ; directed by Robert Joffe.
Robert De Niro, Jeremy Irons.
Keywords: Feature films; Historical films